Telomere content measurement in human hematopoietic cells: Comparative analysis of qPCR and Flow‐FISH techniques. Issue 10 (22nd September 2016) - Wand, Taylor; Fang, Mike; Chen, Christina; Hardy, Nathan; McCoy, J. Philip; Dumitriu, Bogdan; Young, Neal S.; Biancotto, Angélique
Abstract: Abnormal telomere lengths have been linked to cancer and other hematologic disorders. Determination of mean telomere content (MTC) is traditionally performed by Southern blotting and densitometry, giving a mean telomere restriction fragment (TRF) value for the total cell population studied. Here, we compared a quantitative Polymerase Chain Reaction approach (qPCR) and a flow cytometric approach, fluorescence in situ hybridization (Flow‐FISH), to evaluate telomere content distribution in total patient peripheral blood mononuclear cells or specific cell populations. Flow‐FISH is based on in situ hybridization using a fluorescein‐labeled peptide nucleic acid (PNA) (CCCTAA)3 probe and DNA staining with propidium iodide. We showed that both qPCR and Flow‐FISH provide a robust measurement, with Flow‐FISH measuring a relative content longer than qPCR at a single cell approach and that TRF2 fluorescence intensity did not correlate with MTC. Both methods showed comparable telomere content reduction with age, and the rate of relative telomere loss was similar. Published 2016 Wiley Periodicals Inc. This article is a US government work and, as such, is in the public domain in the United States of America.